2021
DOI: 10.3390/en14041174
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Response and Prospects of Clean/Sustainable Energy Transition in Industrial Nations: New Environmental Assessment

Abstract: Coronavirus Disease 2019 (COVID-19) became a pandemic around the world and has huge impacts on our economic and social systems, particularly on the healthcare system and the transportation and energy sectors. To examine a relationship between healthcare and energy sectors in the COVID-19 era, we propose a holistic application of Data Envelopment Analysis for Environmental Assessment (DEA-EA) to assess the COVID-19 response performance of 33 OECD (Organization for Economic Co-operation and Development) nations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…It is hoped that our future studies will address those limitations. See [39][40][41][42] for a general direction on DEA applied to energy and environment.…”
Section: Discussionmentioning
confidence: 99%
“…It is hoped that our future studies will address those limitations. See [39][40][41][42] for a general direction on DEA applied to energy and environment.…”
Section: Discussionmentioning
confidence: 99%
“…Healthcare policymakers and environmental specialists should observe the correlation between the stated factors and devise sustainable healthcare policies to control coronavirus cases in a country. Sueyoshi et al ( 2021 ) analyzed the response of COVID-19 on the clean energy system and healthcare insurance in a panel of 33 OECD countries. They found that healthcare insurance outweighs the negative healthcare concerns associated with the COVID-19 pandemic, leading to sustainable energy transition systems across countries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…To avoid an occurrence of zero in dual variable (i.e., multipliers), this study specifies the following three types of data ranges (R) according to the upper and lower bounds of production factors: Under variable returns to scale, we determine the level of efficiency (θ(k) v ) of the k th DMU as follows:θ(k) v = 1 − Obj(k), where Obj(k) is the optimized objective value of the k th DMU of Equation (A2). See [69][70][71][72][73][74][75][76] for recent DEA developments.…”
Section: Appendix a Network Data Envelopment Analysismentioning
confidence: 99%